Influence of low‐intensity light on phototactic behaviour of Schizothorax oconnori Lloyd. (25th December 2019) - Xu, Jiawei; Lin, Chenyu; Dai, Huichao; Mao, Jingqiao; Ke, Senfan; Yin, Rucheng; Zhang, Ning; Liu, Yan; Shi, Xiaotao
ABSTRACT: In the present study, colour selection and phototaxis experiments were performed on wild subadult Schizothorax oconnori Lloyd. The experimental variables included: five light colours: red, yellow, green, blue, and dark (no light conditions—control), and two flow rates of 0 and 0.3 m/s. Colour selection experiments were conducted to study the preference of S . oconnori to different colours of light in still water and at 10 lx of light intensity. The results showed that the distribution time of S . oconnori in the yellow and green light areas were significantly longer than those in the red and blue light areas ( p  < .05), and the order of preference for the five colours was: green > yellow > black > blue > red. In the phototaxis experiment, the phototactic behaviour of S . oconnori was studied when the light intensity was at 20 lx and the water velocity was at 0 and 0.3 m/s, respectively. The results showed that in both still and dynamic water conditions, S . oconnori displayed positive phototaxis for yellow and green light, and negative phototaxis for red and blue light. S . oconnori displayed weak phototaxis with a light intensity threshold of 0.65 lx–0.80 lx and 1.50 lx–3.05 lx for yellow and green light, respectively. The results suggest that low‐intensity green light could be used for light trapping of S . oconnori . The research may be helpful in the management of fish passage facilities and fisheries.